The Positive Rules for Using Social Media in Marketing Communication Strategy - Rahma, Nur Mifta; Yusmanizar, Yusmanizar; Sukmarini, Andi Vita; Darwis, Muhammad; Prayudi, Prayudi; Purwanda, Nur Widia (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2025)
The use of social media as a marketing communication tool has also had a positive impact. Diverse and interactive content on platforms such as Instagram, Facebook and TikTok help to increase engagement with customers and extend the reach of the Boska Transportama brand. However, companies must be careful in managing social media content to avoid copyright infringement or the spread of misleading information, in accordance with Law Number 11 of 2008 on Electronic Information and Transactions. This study analyzes the marketing communication strategy of CV Boska Transportama and its legal implications. Using a descriptive qualitative approach, this study evaluates five elements of a company’s promotional mix. The results show that the implementation of a comprehensive strategy increases the number of consumers from 6.500 (Year 2022) to 7.000 (Year 2023). The research also identifies legal implications related to consumer protection, personal data, electronic transactions, and business competition that need to be considered in the implementation of marketing strategies. ___ References Books with an author: Kotler, P., Keller, K. L., Ancarani, F., & Costabile, M. (2014). Marketing Management 14/e. Pearson. Journal articles: Ahmad, A., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum Terhadap Konsumen Dalam Transaksi E-Commerce. Jurnal Litigasi Amsir, 10(3), 222-232. https://journalstih.amsir.ac.id/index.php/julia/article/view/249 Alfitriani, A., Octavianty, O., Mutmainna, M., & Pransisto, J. (2022). Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual-Beli Melalui E-Commerce. Jurnal Litigasi Amsir, 24-32. https://journalstih.amsir.ac.id/index.php/julia/article/view/174 Andirwan, A., Putra, P., Alimuddin, F., Tijjang, B., & Hasan, H. (2024). Dinamika Pemasaran PT. TASTI ANUGRAH MANDIRI: Bagaimana Citra Merek, Distribusi, Dan Harga Mempengaruhi Keputusan Pembelian Konsumen. JURNAL MANAJEMEN & ORGANISASI REVIEW (MANOR), 6(1), 84-92. https://doi.org/10.47354/mjo.v6i1.765 Ani, L. S., Arifiah, A., Martodiryo, S., Astyandini, B., Daud, I., Widuri, I. L., & Tijjang, B. (2025). The Role of Social Media Marketing, Brand Image and Products Quality on Purchasing Decisions of SMES Online Shop in Indonesia SME Products to Support the 2030 Sustainable Development Goals (SDGs). Journal of Lifestyle and SDGs Review, 5(3), e04697-e04697. https://doi.org/10.47172/2965-730X.SDGsReview.v5.n03.pe04697 Asmaul, A., Karim, K., & Adhilia, L. T. F. (2023). Perlindungan Hukum Terhadap Pelanggaran Hak Cipta Melalui Internet. Jurnal Litigasi Amsir, 239-253. https://journalstih.amsir.ac.id/index.php/julia/article/view/254 Astuti, T., Purwanda, S., Prasisto, J., & Prayudi, P. (2024). PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN OBAT TANPA IZIN EDAR:(Studi Putusan Nomor 1/Pid. Sus/2023/Pn. Pre). Jurnal Hukum Positum, 9(1), 1-16. https://journal.unsika.ac.id/positum/article/view/11132 Balla, H., Jumardin, J., Kasim, A., & Pappa, A. K. (2024). Peran Locus dan Tempus Delicti dalam Menentukan Kompetensi Pengadilan pada Kasus Kejahatan Siber. Jurnal Litigasi Amsir, 11(4), 390-395. https://journalstih.amsir.ac.id/index.php/julia/article/view/564 Darwis, M., & Amir, R. (2022). Transaksi Trapeutik Sebagai Pertanggungjawaban Dokter Terhadap Pasien. Jurnal Litigasi Amsir, 10(1), 61-71. https://journalstih.amsir.ac.id/index.php/julia/article/view/155 Dewi, M. N. K., Miqat, N., & Purwanda, S. (2024). Analysis of the Legal Substance of Indonesia's Bilateral Investment Treaty (BIT): Balance of Rights and Obligations Based on National Interest. Pena Justisia: Media Komunikasi dan Kajian Hukum, 23(3), 3216-3232. https://doi.org/10.31941/pj.v23i3.5619 Erfan, M., Pransisto, J., & Syahril, M. A. F. (2023). Perlindungan Hukum Bagi Konsumen dari Peredaran Makanan Kedaluwarsa. Jurnal Litigasi Amsir, 10(2), 94-107. https://journalstih.amsir.ac.id/index.php/julia/article/view/228 Farida, F., Rasda, D., & Mutmainna, M. (2023). Implikasi Media Sosial Dalam Tahapan Kampanye Pemilu Serentak Tahun 2024. Vifada Assumption Journal of Law, 1(2), 30-37. https://doi.org/10.70184/gmt7gs45 Pransisto, J., Karim, K., & Syahril, M. A. F. (2022). Mewujudkan Kepastian Hukum Pendaftaran Hak Milik Atas Tanah untuk mencegah Timbulnya Sengketa Tata Usaha Negara. Jurnal Litigasi Amsir, 9(4), 293-303. https://journalstih.amsir.ac.id/index.php/julia/article/view/119